2013
DOI: 10.1097/mcg.0b013e31825c0b69
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Predict the Presence of Missed Synchronous Lesions After Endoscopic Submucosal Dissection for Early Gastric Cancers or Gastric Adenomas?

Abstract: Tumor number at the time of ESD and age could be predictive factors for the presence of missed synchronous lesions after ESD. Careful endoscopic surveillance should be performed after ESD for multiple lesions or for elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…The prevalence of synchronous lesions after endoscopic resection has been reported to be 2.0% to 11.6% [6-8]. The majority of studies reporting the prevalence and diagnosis of synchronous gastric neoplasms have focused on the prevalence after previous endoscopic examinations that were performed within a certain period of time [6,8-10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of synchronous lesions after endoscopic resection has been reported to be 2.0% to 11.6% [6-8]. The majority of studies reporting the prevalence and diagnosis of synchronous gastric neoplasms have focused on the prevalence after previous endoscopic examinations that were performed within a certain period of time [6,8-10].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies reporting the prevalence and diagnosis of synchronous gastric neoplasms have focused on the prevalence after previous endoscopic examinations that were performed within a certain period of time [6,8-10]. Recently, one such study suggested that one-third of those lesions could have been detected during the previous endoscopic examinations [7].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, SMEGC was defined as any second lesions that occurred within 6 months or 1 year after the initial diagnosis of EGC. [8,13,19] However, in the present study, SMEGC was defined as multiple EGC lesions that were found during treatment initially, based on the definition of “synchronous”; in other words, a time interval between lesions was not considered. This difference in the definition may have affected the SMEGC prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that evaluated patients who underwent endoscopic resection, the predictive risk factors of SMEGC were reported to be male sex, undifferentiated histological type, and longitudinal location in the lower third. [11,13,14] In previous studies that evaluated patients who underwent surgical resection, the predictive risk factors of SMEGC were reported to be male sex, depth of invasion, elevated type of gross appearance, LVI, and differentiated histological type. [12,20] In some studies, older age was reported to be a predictive risk factor of SMEGC.…”
Section: Discussionmentioning
confidence: 99%
“…The development of gastric epithelial neoplasm is associated with atrophy or intestinal metaplasia of background mucosa; thus, synchronous multiple lesions are common. The prevalence of synchronous gastric cancer has been reported to range from 4.8% to 20.9% [1-7], and the prevalence of synchronous lesions after endoscopic resection has been reported to be 2.0% to 11.6% [8-10]. Missing synchronous lesions may lead to increased cost for additional procedures or even make the initial endoscopic treatment meaningless, especially when the missed lesion is located more proximally, requiring gastrectomy.…”
mentioning
confidence: 99%